2017
DOI: 10.1103/physrevb.95.161302
|View full text |Cite
|
Sign up to set email alerts
|

Coherent and robust high-fidelity generation of a biexciton in a quantum dot by rapid adiabatic passage

Abstract: A biexciton in a semiconductor quantum dot is a source of polarization-entangled photons with high potential for implementation in scalable systems. Several approaches for nonresonant, resonant, and quasiresonant biexciton preparation exist, but all have their own disadvantages; for instance, low fidelity, timing jitter, incoherence, or sensitivity to experimental parameters. We demonstrate a coherent and robust technique to generate a biexciton in an InGaAs quantum dot with a fidelity close to 1. The main con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
72
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 40 publications
5
72
1
Order By: Relevance
“…In this context and the context of the single-photon amplifier, it is important to understand the intrinsic relaxation mechanisms which can influence preparation and readout of the few-particle quantum states via ultrashort light pulses. To this end, charge-carrier dynamics in QDs based on III-V semiconductors with shallow quantum confinement has been studied both in large ensembles [18][19][20] and single specimens [7,[21][22][23][24][25][26]. These developments have culminated in demonstrations of optical writing and readout of spin states in single or coupled QDs [13][14][15][16][17]27].…”
Section: Introductionmentioning
confidence: 99%
“…In this context and the context of the single-photon amplifier, it is important to understand the intrinsic relaxation mechanisms which can influence preparation and readout of the few-particle quantum states via ultrashort light pulses. To this end, charge-carrier dynamics in QDs based on III-V semiconductors with shallow quantum confinement has been studied both in large ensembles [18][19][20] and single specimens [7,[21][22][23][24][25][26]. These developments have culminated in demonstrations of optical writing and readout of spin states in single or coupled QDs [13][14][15][16][17]27].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in a Rabi oscillation with Gaussian pulses, the splitting between the dressed states increases monotonically from zero such that the full range of phonons is involved in the damping. This second feature also makes the reappearance regime easier to access.Rapid adiabatic passage (RAP) has been demonstrated on single QDs [17,18,24,25], and it has been shown that phonons hinder exciton preparation depending on the sign of the chirp [19,23]. It has been predicted that the reappearance regime translates to a nonmonotonic RAP behavior: At sufficiently high pulse areas RAP improves [11].…”
mentioning
confidence: 99%
“…We therefore present compelling evidence that our system enters the reappearance regime where the electron is effectively decoupled from the phonons. We show that RAP is excellent for phonon-free state preparation.We study a self-assembled InGaAs QD embedded in an n-i-p structure [25] as displayed in Fig. 1(a) and described in the Supplemental Material (SM) [26].…”
mentioning
confidence: 99%
See 2 more Smart Citations